Emotions and ERP information sourcing: the moderating role of expertise. Issue 3 (8th April 2014) - Leger, Pierre-Majorique; Riedl, René; vom Brocke, Jan
Abstract : Purpose: – The purpose of this paper is to report on a laboratory experiment in which the paper investigated how expert and novice users differ in their emotional responses during use of an enterprise resource planning (ERP) system in a decision-making context, and how such a difference affects information sourcing behavior. Design/methodology/approach: – In a simulated SAP business environment, participants' emotional responses were physiologically measured based on electrodermal activity (EDA) while they made business decisions. Findings: – Results show that both expert and novice users exhibit considerable EDA activity during their interaction with the ERP system, indicating that ERP use is an emotional process for both groups. However, the findings also indicate that experts' emotional responses led to their sourcing information from the ERP, while novices' emotional responses led to their sourcing information from other people. Research limitations/implications: – From an academic standpoint, this paper responds to the recent call for more research on the role of emotions for information systems behavior. Practical implications: – The paper discusses the implications of this finding for the development of ERP system trainings. Originality/value: – Because emotions often do not reach users' awareness level, the paper used EDA, a neurophysiological measure, to capture users' emotional responses during ERP decision making, instead of using self-report measures that depend on conscious perception. Based on this method, the paper found that emotions can lead to different behavioral reactions, depending on whether the user is an expert or novice.